Complication of COVID-19: Mild Encephalopathy Syndrome with Reversible Splenial Lesion - Tatiana V. Matveeva; Rustem T. Gaifutdinov; Dinara S. Kamalova; Gulnaz A. Fasakhova (Анналы клинической и экспериментальной неврологии)
A syndrome of mild encephalopathy with reversible splenial lesion (MERS) was described in a post-COVID-19 male patient. The clinical manifestations included neuropsychiatric and visual abnormalities; when focusing separately on an object (one eye closed), the left eye perceived it as normal, but the right eye perceived it as multiple images moving diagonally into the distance. T2, FLAIR, and ADC magnetic resonance imaging (MRI) showed a splenial lesion that resolved rapidly without using corticosteroids. The patient was diagnosed with cerebral polyopia because he saw images arranged in ordered rows after focusing on an object. Differential diagnoses included astigmatism, palinopsia, and polyopic visual hallucinations. Monocular polyopia is explained by anomia associated with the patient's partial split-brain syndrome (the splenial lesion, neuropsychiatric abnormalities); involvement of the pathways from the frontal eye fields to the brainstem structures responsible for initiating extraocular eye movements. The association of neurological complications with prior COVID-19, rapid resolution of symptoms, and MRI lesions without initiating immunosuppressive therapy suggested endotheliopathy as the cause of COVID-19 complications.